Awareness of employees on environmental management system at Maya Sanur Resort and Spa: A study applied to front office department - Antari, Ni Made Winda; Sudiarta, Made; Jendra, I Wayan; Septevany, Elvira (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This study aims to assess the employees' awareness of Environmental Management System (EMS) in the Front Office Department of Maya Sanur Resort and Spa. This research collected data through observations and questionnaire distribution. The research sample employed a saturated sampling technique involving 30 respondents. The questionnaire was distributed to the respondents via a QR barcode with online links. The data obtained from the questionnaire were analyzed using SPSS 26 for Windows software, employing frequency, mean, and standard deviation as data analysis techniques to evaluate the implementation of EMS in the front office department of Maya Sanur Resort and Spa. Additionally, correlation analysis was used to measure the relationship between employees' awareness and the implementation of EMS. The result shows that the correlation analysis results demonstrate a strong correlation between employees' awareness of EMS and its implementation in the front office department of Maya Sanur Resort and Spa, with a correlation coefficient value of 0,671. However, three areas still need to be optimal regarding saving energy. These areas include providing natural ventilation lighting, sub-optimal use of air conditioning, and inadequate rechargeable equipment and batteries, so it takes effort to remind each employee about the importance of implementing an Environmental Management System (EMS) in the front office department to help companies increase their ability to improve environmental quality. Therefore, it is recommended that Maya Sanur Resort and Spa provide training for employees regarding implementing the EMS. This training should be conducted for all front office employees, including daily workers (DW) and trainees, to ensure they understand the importance of implementing the EMS and its impact on the hotel and the environment.